Gastrointestinal Symptoms in 2- to 5-Year-Old Children in the Study to Explore Early Development - Reynolds, Ann M.; Soke, Gnakub N.; Sabourin, Katherine R.; Croen, Lisa A.; Daniels, Julie L.; Fallin, M. Daniele; Kral, Tanja V. E.; Lee, Li- Ching; Newschaffer, Craig J.; Pinto-Martin, Jennifer A.; Schieve, Laura A.; Sims, Amy; et al. (Journal of autism and developmental disorders, 2021)
Gastrointestinal symptoms (GIS) are commonly reported in children with autism spectrum disorder (ASD). This multi-site study evaluated the prevalence of GIS in preschool-aged children with ASD/(n = 672), with other developmental delays (DD)/(n = 938), and children in the general population (POP)/(n = 851). After adjusting for covariates, children in the ASD group were over 3 times more likely to have parent-reported GIS than the POP group, and almost 2 times more likely than the DD group. Children with GIS from all groups had more behavioral and sleep problems. Within the ASD group, children with developmental regression had more GIS than those without; however, there were no differences in autism severity scores between children with and without GIS. These findings have implications for clinical management.